Indonesian Generation Z Consumer Ethnocentrism on Food and Beverage Product - Andriyanty, Reny; Wahab, Dodi (Technium Social Sciences Journal, 2022)
Generation Z is a huge potential in Indonesia economy. They hold important role in the domestic product consumption. The research objective to determine the consumer ethnocentrism of Indonesian generation Z attitude towards consumption of domestic food and beverage products in terms of economic, individual, lifestyle, pro-social motivation, threat perception, and buying inertia. This study used a quantitative descriptive method with 431 samples. The data were analyzed with mutlivariance equations through structural equation modeling. The results showed that economic factors have a significant and positive direct effect to the lifestyle of Generation Z in Indonesia. Individual factors had also a significant and positive direct effect to the lifestyle. Lifestyle had a significant and positive direct effect to the consumer ethnocentrism. Economic variables and individual variables through the mediation of lifestyle had a significant influence on the ethnocentrism of Generation Z in Indonesia.